The relationship between mathematical communication skills and multiple intelligences (Journal of the College of Basic Education, 2022)
The current study aims to identify the nature of the correlation between mathematical communication skills and some types of multiple intelligences (linguistic intelligence, logical intelligence, spatial intelligence) among students of third grades in mathematics departments in basic education colleges in Iraqi universities (Al-Mustansiriya, Diyala, Maysan) through Answer the following questions:1- To what extent do the students of the Department of Mathematics in the Colleges of Basic Education possess mathematical communication skills?2- To what extent do the students of the Department of Mathematics in the Colleges of Basic Education possess multiple intelligences?3- What is the relationship between mathematical communication skills and multiple intelligences among students of the Department of Mathematics in the Colleges of Basic Education?